Linalol and Linalyl Acetate Quantitation in the Essential Oil of Somatic Embryos of Bursera linanoe R. - Larqué, Horacio; Sánchez-Arreola, Eugenio; Arellano-Ostoa, Gregorio; Hernández, Luis R.; Bach, Horacio; Chávez-Montes, Abelardo (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: Mexican artisans use the linaloe tree for the production of handcrafts. The extracted oil from the endangered Mexican tree Bursera linanoe which main components are the terpenes linalol and linalyl acetate is protected because of its excessive exploitation. An alternative to mitigate the deforestation of the linaloe tree is the use of somatic embryos, which can be cultured in vitro. Objectives: In this study, we quantify the yield of linaloe oil extracted from three different linaloe embryogenic lines (LEL) B5, 54, and 2011 cultured in different micropropagation systems. Materials and Methods: Using a microwave technique extraction coupled with a Cleavenger device, it was possible to obtain the essential oil from the somatic embryos of B. linanoe. Results: This study suggest that the tested clones have different proliferation responses, depending on the propagation system culture. The LEL B5 harvested in a permanent immersion system showed the highest growth index (GI= 4.23) as well as the highest concentration of linalol and linalyl acetate with 0.1439 mg/mL and 0.5391 mg/mL respectively, while the LEL 54 harvested in a permanent immersion system and semi-solid, produced the lowest concentration of linalol and linalyl acetate with 0.0090 mg/mL and 0.0923 mg/mL respectively. Conclusion: The proliferation and oil yield varied according to the LEL’s. However, the highest production of the biomass was measured under the TI system type RITA®.
Keywords: Bursera linanoe R.; Linaloe oil; Extraction; Secondary metabolites; Microwaving; Bioreactors